Telaah Kritis Kebijakan Fiskal Perspektif Kaidah Fiqh - Aang Kunaifi (LP3M STITNU Al Hikmah Mojokerto, 2018)
Fiscal policy is a significant instrument that can be used by goverment to actuate, stabilize, and increase public economy productivity. Each of economic system exactly promotes its concept and strategy how to establish healthy, fairly, and wealthy of the public economy. Thus, Sharia has the concept and strategy precisely about the public economy. In fact, that concept and strategy are proved during 14 centuries, since the existence of Muhammad SAW until the Caliphate of Ottomans. This article written according to the reality of the history from the comprehensive sources so that it would give a general accuration of the fiscal policy in Islamic economic. Beside that, Islamic fiscal policy has a strong theological fundamental, because of that it absolutely reasonable to applied. Through each approach: history and theology/qawaid fiqhiyyah, this article tries to contribute or advice for the goverment to create the fairly and wealthy the nations. Keywords: Fiscal Policy, Qawaid Fiqhiyyah.